S-substituted 3,5-dinitrophenyl 1,3,4-oxadiazole-2-thiols and tetrazole-5-thiols as highly efficient antitubercular agents - Karabanovich, Galina; Němeček, Jan; Valášková, Lenka; Carazo, Alejandro; Konečná, Klára; Stolaříková, Jiřina; Hrabálek, Alexandr; Pavliš, Oto; Pávek, Petr; Vávrová, Kateřina; Roh, Jaroslav; Klimešová, Věra (European journal of medicinal chemistry, 2017)
Two new classes of antitubercular agents, namely 5-alkylsulfanyl-1-(3,5-dinitrophenyl)-1H-tetrazoles and 2-alkylsulfanyl-5-(3,5-dinitrophenyl)-1,3,4-oxadiazoles, and their structure-activity relationships are described. These compounds possessed excellent activity against Mycobacterium tuberculosis, including the clinically isolated multidrug (MDR) and extensively drug-resistant (XDR) strains, with no cross resistance with first or second-line anti-TB drugs. The minimum inhibitory concentration (MIC) values of the most promising compounds reached 0.03 μM. Furthermore, these compounds had a highly selective antimycobacterial effect because they were completely inactive against 4 gram positive and 4 gram negative bacteria and eight fungal strains and had low in vitro toxicity for four mammalian cell lines, including hepatic cell lines HepG2 and HuH7. Although the structure-activity relationship study showed that the presence of two nitro groups is highly beneficial for antimycobacterial activity, the analogues with a trifluoromethyl group instead of one of the nitro groups maintained a high antimycobacterial activity, which indicates the possibility for further structural optimization of this class of antitubercular agents.
Keywords: Microbial Sensitivity Tests; Humans; Antitubercular agent; léková rezistence; antituberkulotika; Tuberculosis; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; antifungální látky; Sulfhydryl Compounds; Structure-activity relationships; Tetrazoles; Tetrazole; oxadiazoly; tetrazoly; mikrobiální testy citlivosti; lidé; Hep G2 Cells; Drug Design; Oxadiazole; Oxadiazoles; buňky Hep G2; Antitubercular Agents; Antifungal Agents; Drug Resistance; Mycobacterium tuberculosis; racionální návrh léčiv; sulfhydrylové sloučeniny